The three musketeers - Dumas, Alexandre, 1802-1870.; Vogel, Malvina G.; Pablo Marcos Studio (Edina, Minn. : Abdo Pub., 2002)
In seventeenth-century France, young D'Artagnan initially quarrels with, then befriends, three musketeers and joins them in trying to outwit the enemies of the king and queen.
Originally published: New York : Playmore : Waldman Pub., 1990.
Accelerated Reader AR
Keywords: Adventure and adventurers -- Fiction; France -- History -- Louis XIII, 1610-1643 -- Juvenile fiction; France -- History -- Louis XIII, 1610-1643 -- Fiction